The Natural Compound Climacostol as a Prodrug Strategy Based on pH Activation for Efficient Delivery of Cytotoxic Small Agents - Catalani, Elisabetta; Buonanno, Federico; Lupidi, Gabriele; Bongiorni, Silvia; Belardi, Riccardo; Zecchini, Silvia; Giovarelli, Matteo; Coazzoli, Marco; De Palma, Clara; Perrotta, Cristiana; Clementi, Emilio; Prantera, Giorgio; et al. (Frontiers in Chemistry, 2019)
We synthesised and characterised MOMO as a new small molecule analogue of the cytotoxic natural product climacostol efficiently activated in mild extracellular acidosis. The synthesis of MOMO had a key step in the Wittig olefination for the construction of the carbon-carbon double bond in the alkenyl moiety of climacostol. The possibility of obtaining the target (Z)-alkenyl MOMO derivative in very good yield and without presence of the less active (E)-diastereomer was favored from the methoxymethyl ether (MOM)-protecting group of hydroxyl functions in aromatic ring of climacostol aldehyde intermediate. Of interest, the easy removal of MOM-protecting group in a weakly acidic environment allowed us to obtain a great quantity of climacostol in biologically active (Z)-configuration. Results obtained in free-living ciliates that share the same micro-environment of the climacostol natural producer Climacostomum virens demonstrated that MOMO is well tolerated in a physiological environment, while its cytotoxicity is rapidly and efficiently triggered at pH 6.3. In addition, the cytostatic vs cytotoxic effects of acidified-MOMO can be modulated in a dose-dependent manner. In mouse melanoma cells, MOMO displayed a marked pH-sensitivity since its cytotoxic and apoptotic effects become evident only in mild extracellular acidosis. Data also suggested MOMO being preferentially activated in the unique extra-acidic microenvironment that characterises tumoural cells. Finally, the use of the model organism Drosophila melanogaster fed with an acidic diet supported the efficient activity and oral delivery of MOMO molecule in vivo. MOMO affected oviposition of mating adults and larvae eclosion. Reduced survival of flies was due to lethality during the larval stages while emerging larvae retained their ability to develop into adults. Interestingly, the gut of eclosed larvae exhibited an extended damage (cell death by apoptosis) and the brain tissue was also affected (reduced mitosis), demonstrating that orally activated MOMO efficiently targets different tissues of the developing fly. These results provided a proof-of-concept study on the pH-dependence of MOMO effects. In this respect, MOM-protection emerges as a potential prodrug strategy which deserves to be further investigated for the generation of efficient pH-sensitive small organic molecules as pharmacologically active cytotoxic compounds.